PERAN CATUR GURU DALAM MENDIDIK KARAKTER ANAK SUPUTRA - Eko Adi Saputra; Ketut Budiyasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Teachers' chess teachings in the world of education are something that must run in line withcurrent developments, globalization greatly influences the development of children's character whichhas an impact on the traits and attitudes that lead to young children, the need for in-depth assistanceto understand and apply teacher's chess teachings as a reference in educating suputra childcharacter. This research aims to invite readers to educate young children in the midst of rapiddevelopment so that children remain on the path of Dharma. This research uses descriptivequalitative research methods, and data collection uses observation, interviews and literature study.The results of this research show an understanding of educating young children through the teacher'schess teachings.